Effect Of Clerodendrum Serratum L. Extract In Chemically Induced Ulcerave Colis In Rats - Dr. Jigneshkumar I. Patel; Chetanaben D. Bhoya; Nishita M. Chauhan (Educational Administration: Theory and Practice, 2024)
In this study, we invesgated the impact of Clerodendrum serratum L. on chemically induced ulcerave colis in rats. The roots of Clerodendrum serratum L. were ulized to extract crude methanol for in vivo acvity studies. Ulcerave colis was induced in rats using 25mg TNBS in 50% ethanol via the intrarectal route. Animals were divided into various treatment groups, including a normal control group, a disease control group treated with normal saline, and groups treated with different doses of Clerodendrum serratum L. extract (100mg, 200mg, 400mg) for seven days. Sulfasalazine (120mg/kg) served as the standard drug. Daily monitoring of parameters such as body weight, food-water intake, rectal bleeding, and diarrhoea was conducted. Aer the treatment period, animals were sacrificed for evaluaon of colon length-weight, CMDI, histopathology, and anoxidant parameters (superoxide dismutase, catalase, nitric oxide, and lipid peroxidase acvity). Results indicated a significant improvement in various parameters, suggesng the potenal therapeuc efficacy of Clerodendrum serratum L. extract in TNBS-induced ulcerave colis in rats.